Análise quantitativa de fluoretos nos alginatos para uso odontológico - Braga, A. S.; Catirse, Alma B. C. Elizaur B.; Vaz, Luis Geraldo [UNESP]; Polizello, A. C M; Spadaro, A. C C (My University, 2005)
In this study, the aim was to measure the concentration of fluoride ions in dental alginates and the quantity released from alginate molds immersed in milliQ water, 0.1N hydrochloric acid and artificial saliva. Two separate lots of each of seven brands of alginate commercially available in Brazil were analyzed: Avagel, Deguprint, Hydrogum, Orthoprint, Jeltrate, Jeltrate Plus and Jeltrate Chromatic. Fluoride was measured in each sample by direct potentiometry, using the combined fluoride-ion selective electrode. The brands with the highest fluoride concentrations were Hydrogum (7052.87 μg/g), Jeltrate Plus (6519.68 μg/g) and Orthoprint (6218.18 μg/g). Only in Hydrogum and Jeltrate were different fluoride concentrations found in lots one and two. The various materials showed differences in the amount of fluoride released from the molds into the immersion medium, the mean concentration being highest in Hydrogum and Orthoprint, in all three media. The immersion medium also influenced the release of fluoride, which was lower in saliva than in water and highest in acid. Considering that the concentrations of fluoride found in the alginates tested were high and that various sources of exposure to fluoride exist, there is a need for constant monitoring of alginates intended for dental use.

Este trabalho teve como proposta analisar quantitativamente o conteúdo de fluoretos nos alginatos para uso odontológico e a liberação de fluoretos de moldes desses alginatos em água milliQ, saliva artificial e ácido clorídrico 0,1 mol/l. Foram investigadas sete marcas de alginatos disponíveis comercialmente no Brasil, sendo analisados dois lotes de cada material. As concentrações de fluoretos nas diferentes amostras foram determinadas por potenciometria direta, utilizando o eletrodo seletivo combinado de fluoreto. Os materiais que apresentaram maiores concentrações médias de fluoreto total foram Hydrogum (7052,87µg/g), Jeltrate Plus (6519,68µg/g) e Orthoprint (6218,18µg/g). Apenas os materiais das marcas Hydrogum e Jeltrate apresentaram diferenças nas concentrações de fluoretos entre os lotes um e dois. Os materiais apresentaram diferenças na liberação de fluoretos dos moldes, cujas maiores concentrações médias foram liberadas pelas marcas Hydrogum e Orthoprint. O meio influenciou na liberação de fluoreto, sendo que na saliva foi menor que na água e nesta foi inferior ao ácido. Os moldes dos materiais que mais liberaram fluoretos nos três meios (saliva, água e ácido) foram os do Hydrogum e Orthoprint. Considerando que as concentrações de fluoretos encontradas nos alginatos são altas e que existem diferentes fontes de exposição aos fluoretos, há necessidade de constante monitoramento dos alginatos para uso odontológico. Palavras chaves: Fluoretos, alginato, intoxicação, hidrocolóide irreversível, material dentário.
Quantitative analysis of fluorides in alginates for dental use
Keywords: Alginates; Dental material; Fluoride; Intoxication; Irreversible hydrocolloid; alginic acid; biomedical and dental materials; fluoride; hydrochloric acid; comparative study; electrode; intoxication; potentiometry; saliva